Collaboration Between Ministers and Civil Servants in Finland: A Qualitative Analysis From the Ministers’ Perspective - Eklund, Andreas (Scandinavian Journal of Public Administration, 2025)
The article explores the collaboration between cabinet ministers and civil servants in the Finnish political system from the minister’s perspective. The relationship between politicians and public administration is a classic topic, and an in-depth analysis from the politician’s perspective is essential for gaining a deeper understanding of politico–administrative relations. Although there are many theoretical frameworks for politico–administrative relations, there has been less focus on the individual perspective and how politicians perceive their role. The focus is on how ministers view their role in relation to civil servants and how they describe their collaboration with them. The article draws on 29 interviews with persons who have served as cabinet ministers in Finland between 2000 and 2019. The depictions of how the ministers perceive their role and collaborate with civil servants include some variation. From a theoretical perspective, there are both classic views on the role of civil servants and understandings that emphasize a complementary relationship to a greater extent. A focus on the individual perspective reveals clear variation in the experiences of cabinet ministers, and an analysis focusing on their perspective provides a more nuanced understanding of politico–administrative relations.